Examination of defects and the seed's critical thickness in HVPE‐GaN growth on ammonothermal GaN seed. Issue 5 (16th December 2014) - Sochacki, Tomasz; Amilusik, Mikolaj; Fijalkowski, Michal; Iwinska, Malgorzata; Lucznik, Boleslaw; Weyher, Jan L.; Kamler, Grzegorz; Kucharski, Robert; Grzegory, Izabella; Bockowski, Michal
Abstract It is demonstrated in this paper that 1.9‐mm‐thick gallium nitride grown by Hydride Vapor Phase Epitaxy (HVPE) on an ammonothermally grown GaN seed can reproduce the structural, in terms of defects, properties of the seed. The etch pit density and its correlation to the threading dislocation density in the ammonothermal GaN substrate and the HVPE‐GaN layer is presented and analyzed. However, it has recently been observed that for HVPE‐GaN thicker than 2 mm some additional defects are formed in the new grown material. Therefore, three HVPE growth runs were performed in the same experimental conditions, using three structurally identical ammonothermally grown GaN seeds of different thicknesses. The influence of the thickness of the seeds on the crystallization process and the properties of the HVPE‐GaN layers is shown and discussed.